Scholarly literature in HIV-related lesbian, gay, bisexual, and transgender studies: A bibliometric analysis - Nguyen, Tham Thi; Do, Anh Linh; Nguyen, Long Hoang; Vu, Giang Thu; Dam, Vu Anh Trong; Latkin, Carl A.; Hall, Brian J.; Ho, Cyrus S. H.; Zhang, Melvyn W. B.; Ho, Roger C. M. (Frontiers in Psychology, 2023)
Introduction Lesbian, gay, bisexual, and transgendered (LGBT) people are marginalized and understudied. Analyzing research activity worldwide is vital to better understand their needs in confronting the HIV epidemic. This study aimed to evaluate the global literature to identify the research collaboration, content, and tendency in HIV-related issues among the LGBT populations. Methods Peer-reviewed original articles and reviews were achieved from the Web of Science Core Collection database. Country’s collaborations and co-occurrence of most frequent terms were illustrated by VOSviewer software. The Latent Dirichlet Allocation (LDA) and the linear regression model were utilized to uncover the hidden topics and examine the research trend. Results From 1990 to 2019, a total of 13,096 publications were found. Stigma, sexual risk behaviors and HIV testing were the major topics in the LGBT research during the study period. Among 15 topics, topics about HIV/Sexually transmitted infections (STIs) prevalence, Outcomes of HIV/AIDS care and treatment, and Opportunistic infections in HIV-positive LGBT people showed decreasing attention over years, while other topics had a slight to moderate increase. Discussion Our study underlined the exponential growth of publications on the LGBT population in HIV research, and suggested the importance of performing regional collaborations in improving research capacity. Moreover, further research should focus on examining the manner to increase the coverage of HIV testing and treatment, as well as implement HIV-interventions with low cost and easy to scale-up.